1988
DOI: 10.1038/ki.1988.114
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline prevents the hypoxemia-induced renal hemodynamic changes in rabbits

Abstract: The acute renal effects of hypoxemia and the ability of theophylline to prevent these effects were assessed in anesthetized and mechanically-ventilated newborn and adult rabbits. Renal blood flow (RBF) and glomerular filtration rate (GFR) were determined by the clearance of para-aminohippuric acid and inulin, respectively. Each animal acted as his own control. In 14 newborn rabbits (group 1), hypoxemia was significantly associated with a fall in GFR (-22 +/- 6%) and filtration fraction (-17 +/- 3%) and with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
79
1
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 20 publications
11
79
1
2
Order By: Relevance
“…This water and sodium homeostasis during the neonatal period. The confirms other reports showing that the intrarenal infusion of renal hemodynamic effects of endothelin mimic some of the endothelin induced intense renal vasoconstriction without changes induced by acute hypoxemia in animal models ( 10,12) changing MBP, thus pointing to a local action of endothelin on as well as in human newborns (3 1). r his observation suggests the renal microcirculation (6,22).…”
Section: Discussionsupporting
confidence: 79%
“…This water and sodium homeostasis during the neonatal period. The confirms other reports showing that the intrarenal infusion of renal hemodynamic effects of endothelin mimic some of the endothelin induced intense renal vasoconstriction without changes induced by acute hypoxemia in animal models ( 10,12) changing MBP, thus pointing to a local action of endothelin on as well as in human newborns (3 1). r his observation suggests the renal microcirculation (6,22).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, since 8-PT blocked the decrease in RVC and FBF during 10% 02, this indicates that locally released adenosine did contribute to the renal vasoconstriction induced by moderate hypoxia (see Spielman & Thompson, 1982). Similarly, theophylline blocked the renal vasoconstriction induced by systemic hypoxia in 3-to 12-day-old rabbit kittens (Gouyon & Guignard, 1988). However, as 8-PT had no effect on FVC or FBF during hypoxia, it seems locally released adenosine did not exert a dilator influence upon skeletal muscle vasculature.…”
Section: Responses Evoked In Newborn Pigletsmentioning
confidence: 99%
“…In the newborn rabbit, acute normocapnic hypoxemia induces renal hypoperfusion with decreased GFR and RBF (4,(7)(8)(9). The underlying mechanism of this hypoxemia-induced vasomotor nephropathy still remains controversial.…”
mentioning
confidence: 99%
“…We previously demonstrated that the administration of theophylline, a nonspecific antagonist to adenosine receptors, ameliorates the hypoxemia-induced renal hemodynamic changes seen in the newborn rabbit model (4). Moreover, in neonates with respiratory distress syndrome (12) or perinatal asphyxia (13), as in diuretic-dependent critically ill children (14), the use of theophylline improves diuresis and creatinine clearance.…”
mentioning
confidence: 99%
See 1 more Smart Citation